Consistency implementation of the regulation on young marriage in Indonesia - Darmadi Darmadi (Legality : Jurnal Ilmiah Hukum, 2020)
The amendment of Law Number 1 of 1974 to Law Number 16 of 2019 concerning Marriage, especially Article 7 paragraph (1) concerning the age of marriage for the prospective bride, is equal to the age of the prospective groom, which is 19 years. Meanwhile, young age is that the prospective brides are still under 19 years old. This has indeed been required by the legislators so that the prospective bride and groom have a mature mindset and do not easily marry and divorce in married life but in reality what happens in society can cause new problems, namely the prospective bride and groom together. The objectives of this study were to find out the consistency of the application of article 7 of Law Number 16 of 2019, amendments to Law Number 1 of 1974 regarding the incidence of marriage at a young age, and to determine the impact of marriage at a young age and some of the problems that accompany it. The method of this study was the Juridical Empirical method or sociological research. This research was carried out either through observation and interviews in the form of a Religious Court Decision Letter regarding marriage permits. This was done and demonstrated through data in the field, the point of an empirical approach as a social-cultural reality. The result of this research showed that the consistency of the application of article 7 paragraph 1 regarding the age limit in marriage as stipulated in Law Number 16 of 2019 as a result of the Amendment of Law Number 1 of 1974 concerning Marriage was still not fully implemented. It was proven that there were still many people who not yet aware of the consequences of young marriage. The impact of young marriage was very large from various points of view.